Improved Security Bound of (E/D)WCDM - Nilanjan Datta (Ruhr-Universität Bochum, 2021)
In CRYPTO’16, Cogliati and Seurin proposed a block cipher based nonce based MAC, called Encrypted Wegman-Carter with Davies-Meyer (EWCDM), that gives 2n/3 bit MAC security in the nonce respecting setting and n/2 bit security in the nonce misuse setting, where n is the block size of the underlying block cipher. However, this construction requires two independent block cipher keys. In CRYPTO’18, Datta et al. came up with a single-keyed block cipher based nonce based MAC, called Decrypted Wegman-Carter with Davies-Meyer (DWCDM), that also provides 2n/3 bit MAC security in the nonce respecting setting and n/2 bit security in the nonce misuse setting. However, the drawback of DWCDM is that it takes only 2n/3 bit nonce. In fact, authors have shown that DWCDM cannot achieve beyond the birthday bound security with n bit nonces. In this paper, we prove that DWCDM with 3n/4 bit nonces provides MAC security up to O(23n/4) MAC queries against all nonce respecting adversaries. We also improve the MAC bound of EWCDM from 2n/3 bit to 3n/4 bit. The backbone of these two results is a refined treatment of extended mirror theory that systematically estimates the number of solutions to a system of bivariate affine equations and non-equations, which we apply on the security proofs of the constructions to achieve 3n/4 bit security.